2021
DOI: 10.1371/journal.pone.0255316
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severity and mortality in multiple sclerosis are not associated with immunotherapy: Insights from a nation-wide Austrian registry

Abstract: Background The COVID-19 pandemic challenges neurologists in counselling patients with multiple sclerosis (pwMS) regarding their risk by SARS-CoV-2 and in guiding disease-modifying treatment (DMT). Objective To characterize the prevalence and outcome of COVID-19 in pwMS specifically associated with different DMT in a nationwide population-based study. Methods We included patients aged ≥18 years with a confirmed diagnosis of MS and a diagnosis of COVID-19 established between January 1, 2020 and December 31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 33 publications
4
24
2
2
Order By: Relevance
“…The Austrian MS-COVID-19 registry (AUT-MuSC), a collaboration of MS centres certified by the Austrian Neurological Society (ÖGN) adhering to a common and controlled quality standard of excellence, documents epidemiological, clinical and paraclinical data of pwMS suffering a SARS-CoV-2 infection, as described in detail elsewhere. 9 …”
Section: Methodsmentioning
confidence: 99%
“…The Austrian MS-COVID-19 registry (AUT-MuSC), a collaboration of MS centres certified by the Austrian Neurological Society (ÖGN) adhering to a common and controlled quality standard of excellence, documents epidemiological, clinical and paraclinical data of pwMS suffering a SARS-CoV-2 infection, as described in detail elsewhere. 9 …”
Section: Methodsmentioning
confidence: 99%
“…Consistently, in a North American study, both ocrelizumab and rituximab were associated with hospitalization, but association was stronger for rituximab (Salter et al, 2021). However, the role of anti-CD20 treatments in the COVID-19 severity were not always confirmed (Bsteh et al, 2021;Louapre et al, 2020). Therefore, it is relevant to undertake a comprehensive systematic review for estimating the mortality rate among patients under these therapies, for exploring all their available characteristics and in general for estimating their rates of severe COVID-19 events.…”
Section: Introductionmentioning
confidence: 93%
“…All selected articles were rigorously appraised by two authors according to a modified version of the Dutch Cochrane center critical review checklist proposed by MOOSE (Stroup et al, 2000). Key domains assessed by the MOOSE tool include: (I) Clear definition of study population; (II) Clear definition of outcomes and outcomes assessment; (III) Independent assessment of outcome parameters; (IV) Sufficient The presence of SARS-CoV2 antibodies in MS patients (Armstrong et al, 2021;Arrambide et al, 2021;Barzegar et al, 2020Barzegar et al, , 2021Bose and Galetta, 2021;Bsteh et al, 2021;Chaudhry et al, 2020;Ciampi et al, 2020;Conte, 2020;Czarnowska et al, 2021;D'Abramo et al, 2021;Devogelaere et al, 2020;Fernandez-Diaz et al, 2021;Fragoso et al, 2021;Garg et al, 2020;Hervas-Garcia, 2020;Loonstra et al, 2020;Louapre et al, 2020;Montero-Escribano et al, 2020;Olivares Gazca et al, 2020;Sahraian et al, 2020;Salter et al, 2021;Sen et al, 2021;Sormani et al, 2021b,a;Spelman et al, 2021;Stroup et al, 2000;Suwanwongse and Shabarek, 2020;Thornton and Harel, 2020 *Data provided by the authors but not published.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…However, caution should be exerted when interpreting these types of data since they rely on spontaneous reporting with difficulties in completely controlling for confounders. In addition, in persons with MS (pwMS), established risk factors seem to outweigh the impact of disease-modulatory therapies (DMTs) on COVID-19 outcomes (Bsteh et al, 2021;Louapre et al, 2020;Zabalza et al, 2020). Nevertheless, a recent pre-pandemic study showed an increased rate of severe infections with B cell depletion compared to other DMTs in pwMS (Luna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%